Exploring The Millennial Learners’ Attributes and Needs in Educational Environment - Siti Hajar Larekeng; Abdul Hakim Yassi; Muhammad Najib; Badaruddin Badaruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Millennial learners were born and raised in the digital era, with a variety of technology complete and sophisticated, such as: computer, laptop/notebook/netbook, smart Phone, iPads, PDA, MP3 player,  internet, and various other electronic devices. From childhood, they were familiar or introduced with the sophisticated gadgets that directly or indirectly influence their behavioral development and personality. Millennial generation has characteristics of behavior and personality that is different from previous generation. The attributes of millennial learners who grown up with technology may influence the current teaching strategy. In supporting the urgency of exploring the millennial learners’ attributes and needs in educational environment, the authors conduct a survey at Education Faculty of Universitas Muhammadiyah Parepare (UM Parepare), especially the learners who are majoring in English Education.The survey confirmed that those learners were exposed to various types of IT application. Some indications can be extracted from this study. Firstly, the learners were reasonably comfortable in utilizing various types of IT tools and expected the application to be embedded in the current application of learning. Secondly, the learners preferred to try to web in obtaining information, so the use of internet to access learning materials are highly needed. Last but not least, learners were mostly rated to adopt most ICT tools and devices.